KORUPSI DAN UPAYA PEMBERANTASANNYA PERSPRKTIF HUKUM ISLAM - Ratno, Dedi (INTEGRATIF |Jurnal Magister Pendidikan Agama Islam, 2025)
Corruption is an extraordinary crime because it has a negative impact on all aspects of life. This crime has the potential to bring misery, impoverishment and suffering to many people. Corruption occurs due to many factors such as hedonism, weak leadership, lack of religious and moral education, and others. Therefore, how does Islam view the crime of corruption and how to eradicate it. The aim is to find out the Islamic view in overcoming this problem. With the method used in this study, namely the library research method or literature by collecting various sources and comparing them with other sources. The word corruption literally means rottenness, badness, dishonesty, can be bribed, immoral, deviation from holiness. The Islamic perspective of corruption has an understanding of riswah, sariqah, and traitor. There are many factors that cause corruption, one of which is the perspective of wealth, and a materialistic lifestyle. Therefore, the sanctions for perpetrators of corruption from an Islamic perspective include hudud and takzir. So a strategy is also needed in its eradication, one of which is by implementing criminal law. Corruption is also a very bad crime and can cause harm to all people, especially the lower classes. Therefore, in Islam there are sanctions in the form of hudud and takzir for perpetrators of corruption, in addition, the efforts that we can make to eradicate it through criminal justice are focused on the repressive nature